OPTIMASI KONDISI PIROLISIS SAMPAH BAMBU GUNA MENDAPATKAN ENERGI TERBESAR - D A. Himawanto (BUANA SAINS, 2012)
The aim of this experiment was to evaluate optimum condition of process pyrolisis bamboo biomass to reach the highest energy. The early activities was to collect bamboo biomass and to dried untill the maximum water content around 10%, and to crash under 20 mesh. Raw material to evaluate by proximate and heating value as standart as ASTM 2015. Standart evaluation for water content used ASTM D-3173, ash value by ASTM D-3174, volatile content by ASTM D-31175 and fixed carbon content by ASTM D-3172. Pyrolisis process by used raw material about 20 g, and increased temperatures with heating rate 10oC/second untill reach final temperature 300oC, 400oC and 500oC with variation holding time 15, 30 and 45 minute. Result of the research showed that variation holding time and final temperature give the minimum energy and is due probably cracking on char